Movements and timing of humpback whales (Megaptera novaeangliae) within the breeding region of the Eastern South Pacific - Valdivia, Camila A. (2017)
This study highlights the importance of monitoring movements of humpback whales within the breeding area of the eastern South Pacific as in other regions. In future studies, we recommend including photographs from Colombia to cover the entire breeding area as well as to increase telemetry studies, which would enhance our understanding of humpback whale movements during the breeding season.